ASSESSMENT OF TASKS CREATED BY CHATGPT-4o FOR 10-YEAR-OLDS IN THE FIELD OF MAGNETISM - Miščević, Gordana; Starijaš, Gorana; Petrović, Ivana (Metodička teorija i praksa, 2025)
This paper examines the potential of ChatGPT4o as a support tool in Nature and Society teaching for fourth-grade students. Tasks of three levels of complexity in the domain of magnetism were generated by the tool and evaluated by 12 experts using a Likert scale. The results indicate that the generated tasks are age-appropriate, with the basic-level tasks receiving the highest evaluations. The analysis focused on aspects such as safety, promotion of student cooperation, alignment with learning outcomes, real-life application, and clarity. Certain shortcomings were noted, particularly in terms of safety in task implementation and the need for clearer instructional guidelines. The paper discusses the implications for future use of AI-based systems in elementary education and emphasizes the necessity of teacher training for responsible implementation of such technologies.